Fabrication of Cerium Oxide-Graphene Oxide Nanocomposite using Ultrasound-Assisted Precipitation Method - Iis Nurhasanah; Arvia Arvia; Nor Basid Adiwibawa Prasetya; Ahmad Jauhari (Department of Physics, Sebelas Maret University, 2024)
The cerium oxide-graphene oxide nanocomposite was fabricated by ultrasound-assisted precipitation method and characterized using Fourier transform infrared, UV-Vis spectroscopy, X-ray diffractometer, and transmission electron microscope. The Fourier transform infrared spectra displayed the vibrations of O-H, C=C, and C-H indicating the interaction between cerium oxide and graphene oxide. The broad absorption of around 300 nm is ascribed to the superposition of cerium oxide and graphene oxide absorption peaks. X-ray diffraction pattern analysis suggests the creation of graphene oxide nanosheets with an interlayer spacing of 0.821 nm. The transmission electron microscope image showed that the cerium oxide nanoparticles dispersed on the graphene oxide nanosheet. These findings exhibit the useful ultrasound-assisted precipitation method for fabricating cerium oxide-graphene oxide nanocomposite.